The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ehf2.12587
|View full text |Cite
|
Sign up to set email alerts
|

Hypochloraemia and 30 day readmission rate in patients with acute decompensated heart failure

Abstract: Aims Despite recent advances in guideline-directed therapy, rehospitalization rates for acute decompensated heart failure (ADHF) remain high. Recently published studies demonstrated the emerging role of hypochloraemia as a predictor of poor outcomes in patients with ADHF. This study sought to determine the correlation between low serum chloride and 30 day hospital readmission in patients with ADHF. Methods and resultsWe retrospectively reviewed electronic medical records of 1504 patients who were admitted to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
1
14
1
2
Order By: Relevance
“…In clinical terms, hypochloremia manifests itself by non-specific symptoms noticeable primarily in metabolic alkalosis (if developing) including apathy, confusion, cardiac arrhythmias, and increased muscle irritability (caused by decreased ionized calcium concentrations) (Marchenko et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical terms, hypochloremia manifests itself by non-specific symptoms noticeable primarily in metabolic alkalosis (if developing) including apathy, confusion, cardiac arrhythmias, and increased muscle irritability (caused by decreased ionized calcium concentrations) (Marchenko et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation on the association between hypochloremia and rehospitalization was done by Marchenko et al [28]. In their study, hypochloremia on either admission or discharge was found to be independently associated with a greater 30-day readmission rate.…”
Section: Clinical Trials -Chloride In Acute Hfmentioning
confidence: 95%
“…Consistent with this idea, patients with hypochloraemia take higher doses of loop diuretics than those with normal chloride levels [ 3 12 ], but whether a high-dose diuretic is the cause of hypochloraemia or becomes necessary because of hypochloraemia-induced diuretic resistance is uncertain.…”
Section: Chloride and Outcomementioning
confidence: 99%
“…Hypochloraemia is a common electrolyte disturbance and marker of adverse outcome amongst patients with HF independent of other prognostic markers, including hyponatremia (Table 1 ) [ 3 12 ]. The mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%